Efek Hepatoprotektif Tanaman Obat - Palawe, Christesa Y.; Kairupan, Carla F.; Lintong, Poppy M. (Universitas Sam Ratulangi, 2021)
Abstract: Medicinal plant that contain antioxidants is an alternative therapeutic option for liver disorders. This study was aimed to review the hepatoprotective effects of medicinal plants. This was a literature review study using PubMed, Google Scholar and Clinical Key. The results showed 10 hepatoprotective medicinal plants, as follows: Â soursop leaves, yellow bamboo shoots, moringa leaves, green betel leaves, libo fruit, kenikir, neem leaves, bitter bean seeds, black cumin, and solo garlic. All of them showed hepatoprotective activities based on the results of the tests, using biochemical and histopathological parameters. Soursop leaves could increase SOD level and reduce MDA level; yellow bamboo shoots were demonstrated to maintain SGPT activities and bilirubin level; moringa leaves have been associated with the reduction of MDA, SGOT, and SGPT levels; green betel leaves were able to reduce SGOT and SGPT levels and improve liver centrolobular necrosis; libo fruit was able to lower SGPT level; kenikir and bitter bean seeds were shown to reduce SGOT and SGPT levels; neem leaves were associated with the reduction of ALT level and protection against liver cell damage; black cumin was found to reduce fat degeneration; solo garlic could reduce MDA, SGPT, and SGOT levels, and maintain SOD level. In conclusion, the 10 hepatoprotective medicinal plants have the ability to increase SOD levels, reduce SGOT, SGPT and MDA levels, maintain bilirubin levels, regenerate centrilobular necrosis of the liver, and reduce fat degeneration of the liver. Solo garlic shows the largest amount of hepatoprotective activities, followed by yellow bamboo shoots, green betel leaves and libo fruit.Keywords: medicinal plants, hepatoprotector effectÂ Â Abstrak: Pengobatan menggunakan tanaman obat yang mengandung antioksidan merupakan pilihan terapi alternatif untuk gangguan pada hati. Penelitian ini bertujuan untuk menelaah efek hepatoprotektif tanaman obat. Jenis penelitian ialah literature review dengan menggunakan PubMed, Google Scholar dan Clinical Key. Hasil penelitian mendapatkan 10 tanaman obat hepatoprotektor yaitu daun sirsak, rebung bambu kuning, daun kelor, daun sirih hijau, buah libo, kenikir, daun mimba, biji petai, jintan hitam, dan bawang lanang. Tanaman-tanaman obat tersebut memiliki aktivitas hepatoprotektif berdasarkan pengujian dengan parameter biokimia dan histopatologi. Daun sirsak dapat meningkatkan kadar SOD dan menurunkan kadar MDA; rebung bambu kuning dapat mempertahankan aktivitas SGPT dan kadar bilirubin; daun kelor menurunkan kadar MDA, SGOT, dan SGPT; daun sirih hijau menurunkan kadar SGOT dan SGPT, serta memperbaiki nekrosis sentrolobuler hati; buah libo menurunkan kadar SGPT; kenikir dan biji petai menurunkan kadar SGOT dan SGPT; daun mimba menurunkan kadar SGPT dan memiliki daya proteksi terhadap kerusakan sel hati; jintan hitam dapat mengurangi degenerasi lemak; bawang lanang menekan peningkatan kadar MDA, SGPT, SGOT dan mempertahankan kadar SOD. Simpulan penelitian ini Kesepuluh tanaman obat hepatoprotektor tersebut memiliki kemampuan dalam meningkatkan kadar SOD, menurunkan kadar SGOT, SGPT dan MDA, mempertahankan kadar bilirubin, memperbaiki nekrosis sentrolobuler hati, dan mengurangi degenerasi lemak hati. Bawang lanang menunjukkan aktivitas hepatoprotektor terbesar, diikuti rebung bambu kuning, daun sirih hijau, dan buah libo.Kata kunci: tanaman obat, efek hepatoprotektor